2010
DOI: 10.18632/aging.100162
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 reduces endothelial activation without affecting vascular function in ApoE-/- mice

Abstract: Excessive production of reactive oxygen species (ROS) contributes to progression of atherosclerosis, at least in part by causing endothelial dysfunction and inflammatory activation. The class III histone deacetylase SIRT1 has been implicated in extension of lifespan. In the vasculature,SIRT1 gain-of-function using SIRT1 overexpression or activation has been shown to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(116 citation statements)
references
References 27 publications
3
110
0
3
Order By: Relevance
“…It suggests that SIRT1 has a compensatory upregulation in endothelial cells in response to inflammatory factors. Moreover, expression of ICAM-1 was found to be increased in atherosclerotic plaques of ApoE / SIRT1 +/ mice compared with ApoE / SIRT1 +/+ mice [17]. Furthermore, we demonstrated that SIRT1 significantly inhibited PMA/Io-induced ICAM-1 expression in HUVECs to 50%.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…It suggests that SIRT1 has a compensatory upregulation in endothelial cells in response to inflammatory factors. Moreover, expression of ICAM-1 was found to be increased in atherosclerotic plaques of ApoE / SIRT1 +/ mice compared with ApoE / SIRT1 +/+ mice [17]. Furthermore, we demonstrated that SIRT1 significantly inhibited PMA/Io-induced ICAM-1 expression in HUVECs to 50%.…”
Section: Discussionmentioning
confidence: 61%
“…We have previously shown that transgenic mice that overexpress SIRT1 in the vascular endothelium have better endothelium-dependent vasodilation and fewer atherosclerotic lesions when fed a high-fat diet [16]. Recently, expression of ICAM-1 was increased in atherosclerotic plaques of ApoE / SIRT1 +/ compared with ApoE / SIRT1 +/+ mice [17]. However, the mechanism by which SIRT1 regulates ICAM-1 expression remains unknown.…”
mentioning
confidence: 99%
“…So, in the vasculature, SIRT1 gain-of-function using SIRT1 overexpression has been shown to improve endothelial function in mice. Subsequently, it was described that SIRT1 does not directly inluence endothelium-dependent vascular function in ApoE−/− mice, but it improves vascular function by preventing superoxide production in ECs and reduces the expression of inlammatory adhesion molecules by suppressing NF-κB signalling [58].…”
Section: Atherosclerosismentioning
confidence: 99%
“…Потаскалова запалення через інгібування сигналів NF-κB і зниження рівня експресії ICAM-1 і VCAM-1. Доведено, що ресвератрол підвищує актив-ність eNOS і підтримує нормальну функцію ендотелію [48].…”
Section: можливості профілактики та лікування аг через епігенетичні вunclassified